Recent Advances in Deep Learning and Medical Imaging for Cancer Treatment (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint includes a collection of recent articles on the identification, staging, diagnosis, and classification of malignant biliary structures, leukemia, bladder cancer, colorectal and osteosarcoma cancer, oral cancer, breast cancer, lung nodules, liver tumors, pulmonary diseases, skin cancer, metabolic tumor, and laryngeal carcinoma. It also includes items on the use of computer-aided, deep learning, and medical imaging-based cancer detection and diagnosis.